Concomitant high-risk pulmonary embolism and subdural hematoma: endo-vascular system thrombolysis as a possible solution to a difficult challenge - Vincenza Clelia Alvich; Marco Valentini; Debora Monti; Stefano Perlini; Francesco Salinaro (Emergency Care Journal, 2023)
Acute pulmonary embolism (PE) is a challenging and potentially fatal cardiovascular disorder. In high-risk patients, percutaneous catheter embolectomy may be considered when thrombolysis is contraindicated or has failed. We hereby discuss the case of a 60-year-old man who was found unconscious on the ground with signs of head trauma and respiratory failure. He was found to have a massive pulmonary embolism and multiple basilar skull fractures associated with slight subdural and subarachnoid hemorrhages. His acute treatment required a multidisciplinary discussion and approach. EkoSonic™ Endovascular System (EKOS) thrombolysis was successfully performed. The patient required intensive care unit (ICU) monitoring and treatment for 31 days. Upon discharge, henoxaparin 4000 UI twice per day was prescribed as anticoagulant, without any evidence of pulmonary hypertension or severe neurological sequelae.